Capacitance-Voltage characteristics of nanowire trigate MOSFET considering wave function penetration (Global Journals of Research in Engineering, 2012)
Capacitance is the heart of MOSFET because of its application in the real life. Capacitance indicates switching speed of the MOSFET. It is our goal to minimize capacitance as possible as we can in MOSFET. Due to our necessary to compact the Integrated Circuit as possible as we can for getting small electronics devices. Capacitance determine the speed of the IC. Every engineer in this section should know capacitance of his implementing device MOSFET to get exert result from this device. Whenever we deal with 10X10 nm scale or less device of MOSFET. We must be concerned the effect of wave function penetration into device in this stage classical mechanics fails to describe exact result of the system because electron can move in only one direction (say x) where in 3Dimention, it cannot move in other two direction (y, z). i.e. confined in two direction which is not predictable by classical mechanics here quantum mechanics (QM) gives better solution of this problem. Therefore we consider QM in our study. Here we presented how wave function play vital role when you consider small area of trigate MOSFET. This result will be helpful when you are determining capacitance of trigate MOSFET.
Keywords: Trigate MOSFET; wavefunction penetration; classical mechanics